1980
DOI: 10.1161/01.str.11.6.643
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profile of vertebrobasilar territory infarction. Prognostic implications.

Abstract: SUMMARY To determine the type and prognostic significance of the various temporal profiles of vertebrobasilar territory infarction, 39 consecutive patients were studied.The following temporal profiles were identified: 1) coma from onset, 5 patients; 2) sudden onset followed by stabilization, 12 patients; 3) gradual onset reaching stabilization within 24 hours, 7 patients; 4) gradual onset with progression beyond 24 hours, 2 patients, and; 5) delayed worsening after stabilization, 13 patients. Patients in Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(28 citation statements)
references
References 30 publications
3
24
1
Order By: Relevance
“…Study by Patrick et al found that most common clinical presentation was cranial nerve involvement was 64%, followed by altered sensorium (47%). 9 Kora et al study found most common presentation as motor disturbance and altered sensorium (63%) patients. In posterior circulation stroke is due to the involvement of cerebellum or its connections.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Study by Patrick et al found that most common clinical presentation was cranial nerve involvement was 64%, followed by altered sensorium (47%). 9 Kora et al study found most common presentation as motor disturbance and altered sensorium (63%) patients. In posterior circulation stroke is due to the involvement of cerebellum or its connections.…”
Section: Resultsmentioning
confidence: 94%
“…8 Patrick et al showed a mortality of 25.6%. 9 Jone et al study showed mortality of 27.5%. 16 Kora et al study showed mortality of 26.3%.…”
Section: Resultsmentioning
confidence: 94%
“…15 Jones, Millikan and Sandok reported 37 cases examined between 1967 and 1969. 9 Patrick, Ramirez-Lassepas and Snyder reported 22 clinical cases collected from 1975 to 1978 with CT. 23 Irino et al reported 2 clinical cases with serial angiography and CT. 5 Thus at the present time, clinical data can be based on 62 patients with carotid artery infarction, 48 of whom had no CT and on the data from 47 patients with vertebrobasilar infarctions 23 of whom had no CT. Thorough clinico-pathological reports are available for patients with 3 vertebrobasilar and 1 carotid lesion.…”
Section: Vertebrobasilar Territorymentioning
confidence: 99%
“…Occlusions of large arteries Atherosclerotic thrombosis of large arteries is generally held as the main cause of progressing stroke 3 ' 5 -9 -l5 ' 23 but the former equation stroke-in-evolution = thrombosis-inevolution is no longer warranted. 4 Cardiac embolism can also cause a stroke-in-progression.…”
Section: Different Causesmentioning
confidence: 99%
See 1 more Smart Citation